Hepatitis C elimination among people incarcerated in prisons: challenges and recommendations for action within a health systems framework. (May 2021) - Akiyama, Matthew J; Kronfli, Nadine; Cabezas, Joaquin; Sheehan, Yumi; Thurairajah, Prem H; Lines, Richard; Lloyd, Andrew R
Summary: Hepatitis C virus (HCV) is a global public health problem in correctional settings. The International Network on Health and Hepatitis in Substance Users–Prisons Network is a special interest group committed to advancing scientific knowledge exchange and advocacy for HCV prevention and care in correctional settings. In this Review, we highlight seven priority areas and best practices for improving HCV care in correctional settings: changing political will, ensuring access to HCV diagnosis and testing, promoting optimal models of HCV care and treatment, improving surveillance and monitoring of the HCV care cascade, reducing stigma and tackling the social determinants of health inequalities, implementing HCV prevention and harm reduction programmes, and advancing prison-based research.